The relationship of internal auditors' characteristics with external auditors' reliance and its impact on audit efficiency: Empirical evidence from Indonesian government institutions - Rudy Usman; Abdul Rohman; Dwi Ratmono (Cogent Business & Management, 2023)
Previous studies have separately investigated the relationship between the internal auditors' characteristics, the level of external auditors' reliance, and the audit efficiency so it has not fully described how the external auditors make decisions to rely on internal audit work, which has an impact on audit efficiency. Therefore, the current study aims to fill the research gap by analyzing the relationship among the internal auditors' characteristics, external auditors' reliance and audit efficiency in one comprehensive research model with the institutional environment as a moderating variable in the relationship between the level of external auditors' reliance and the audit efficiency. This study is conducted in government organizations with the consideration that the reliance of external auditors on internal audit work is one of the strategies for dealing with the limited resources faced by government external auditors in Indonesia. Surveys are conducted to collect research data. The research subjects are 164 external auditors (BPK) from 34 representative offices in Indonesia. The data are analyzed using Partial least Square-Structural Equation Modeling. The results of this study show that the level of external auditors' reliance on internal audit work has a significant effect on audit efficiency. Furthermore, the results also show that there is a moderating effect of the institutional environment on the relationship between the level of external auditors' reliance and audit efficiency. This study contributes to the application and development of relational coordination theory and institutional theory in accounting and auditing fields, especially in government sector audits.
Keywords: M410; M420; M480; 650; Accounting; audit efficiency; auditing; external auditors; institutional environment; internal auditors; level of reliance; public sector accounting